Physical and combustion characteristics of densified palm biomass - Hasan, Mohd. Faizal (2009)
As reported by Malaysia Palm Oil Statistics, the production of palm biomass residues increased significantly from year to year. Thus, the utilization of these residues is very important in order to prevent waste and dump areas adjacent to the palm oil mills. Meanwhile, in order to increase the energy content per unit volume, briquetting technology is expected to fulfill this requirement by compacting biomass residues into form with higher density. In this project, the utilization of empty fruit bunch (EFB) is emphasized in briquette production. It is combined with mesocarp fibre in order to obtain the higher gross calorific value of briquette. The result shows that the briquette contains EFB fibre and mesocarp fibre (weight ratio 60:40) has the compressive strength and combustion characteristics which are competitive with local commercial briquette contains mesocarp fibre and shell (weight ratio 60:40). It is found that combustion rate belongs to briquette containing proposed mixture (EFB and mesocarp fibre) is higher than the rate belongs to another one, if both of them are produced under same compaction pressure. This gives a higher heat release from the combustion of proposed briquette. Besides, all the characteristics belong to briquette contains new mixture are found to be close to the minimum requirement for making commercial briquette which stated by DIN 51731.